The Role of Servant leadership in Team Performance Mediated by Team Cohesion (Case Study: Teams of Secondary School Teachers in Kurdistan Province) - Jamal Abdolmaleki; Siroos ghanbari (Shahid Chamran University of Ahvaz, 2021)
IntroductionIn recent decades, organizations around the world have done teamwork to provide faster, more flexible, and more adaptable responses in turbulent and complex work environments. The importance and application of teamwork has increased dramatically in the last three decades in the field of education and professional organizations. With the increasing use of teams in organizations, research has begun focusing on the role of leadership in increasing team success. Positive support from Servant leaders for all followers increases team cohesion, which affects team members' focus, enthusiasm and commitment to tasks and goals, thereby increasing team performance.But in order for servant leadership to gain more legitimacy as a theory of leadership, research needs to examine how this leadership style can play a role in team cohesion and teacher team performance. And is this valid in educational organizations as well or not? Take action. Therefore, the purpose of the present study is to investigate the role of servant leadership in team cohesion and team performance along with the mediating role of team cohesion in the relationship between servant leadership and team performance in teacher teams.MethodThe study population was all secondary school teachers in Kurdistan province, which was selected by stratified random sampling method and based on Cochran's formula, a sample of 346 teachers. The research method was quantitative and correlational and the modeling approach was covariance-based structural equation. Data were collected using the Leiden et al.'s (2015) Servant Leadership Questionnaire, Podsakoff and MacKenzie (1994) Team Cohesion Questionnaire, and the Puente-Palacios, Martins and Palumbo (2016) Team Performance Questionnaire. The reliability and validity of the questionnaires were assessed by Cronbach's alpha techniques and confirmatory factor analysis. Confirmation path analysis was used to analyze the data using lisrel software. ResultsThe results showed that servant leadership and team cohesion have a positive effect on teachers' team performance at the level of 0.05; Servant leadership due to team cohesion has a positive and significant effect on the variable of team performance of teachers at the level of 0.05.DiscussionBecause servant leadership at the team level is also involved in the exchange process, leaders help the team by acknowledging the team's strengths and potentials, as well as its overall support. It can be said that servant leadership is an important factor in creating team cohesion and improving team performance in teacher teams.